Worldscope meets Compustat: A comparison of financial databases - Niels Ulbricht; Christian Weiner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
With this study we are the first to systematically compare today's two major counterparts as a source of accounting and financial data for researchers: Compustat North America by Standard & Poor's and Worldscope by Thomson Financial. This investigation is conducted for U.S. and partly Canadian data over an extensive period from 1985 to 2003. We examine more than 650 data items available in both databases and address the question of whether or not the decision for one or the other source may have an impact on the outcome of research projects. It is probably commonly assumed that this impact is minor, but it also leaves room to question certain results. We show that the use of both databases should lead to comparable results, but also find that if, e.g. a size bias, is not treated with care the quality of results may differ considerable. Furthermore after 1998 the number of firms covered by Worldscope exceeds the one covered by Compustat by about one fourth.
Keywords: 330